Analysis of Purchasing Decisions Based on Sales Promotion and Service Quality - Maddinsyah, Ali (Program Pascasarjana Universitas Negeri Makassar, 2020)
This research aims to analyze purchasing decisions based on sales promotions and service quality at Giant Ekspres Pondok Cabe, South Tangerang. The method of data analysis is using quantitative associative analysis techniques where the population is 32,866 consumers, sampling, the author uses the Slovin formula with an error rate of 10% where after calculating the number of samples obtained as much as 99.69 rounded up to 100 Respondents. There is a significant simultaneous effect between sales promotion and service quality on purchasing decisions at Giant Express Pondok Cabe. This is indicated by the value of Fcount> Ftable (1990,740> 3.09) and significance of 0,000. The effect is based on the value of the R determination coefficient which is equal to 0.976. This means that variations in Sales Promotion and Service Quality variables explain the variation in the purchase decision variable is 97.6% and the difference of 2.4% is explained by factors that are not examined.Â